Variations in Duchenne muscular dystrophy course in a multi‐ethnic UK population: potential influence of socio‐economic factors. (16th May 2017) - Hufton, Margaret; Roper, Helen
Abstract : Aim: To explore variation in clinical course and steroid treatment in Duchenne muscular dystrophy (DMD) by ethnic origin and socio‐economic status. Method: In this longitudinal cohort study, clinical outcome was defined as age at loss of ambulation (LOA). Ages are presented as months for accurate calculation. Steroid use was reviewed against national guidelines. Kaplan–Meier survival analysis was used to determine probabilities over time of LOA. Log‐rank test was used to evaluate comparisons between ethnic and socio‐economic groups. Results: From 2005 to 2014, 71 children were newly diagnosed with DMD. Complete data were available on 69, including 33 of white British heritage and 23 of South Asian heritage. Mean age at diagnosis (without known family history) was 45.7 months; white British ethnicity 42.1 months (range 14–86mo), South Asian ethnicity 50.2 months (range 5–98mo). Twenty‐four males lost ambulation. Those of South Asian heritage lost ambulation earlier (mean LOA 105.8mo [8y 10mo]) than those of white British heritage (mean LOA 117.8mo [9y 10mo]): log‐rank test score 0.012 ( p <0.05). Those most deprived did worse: mean age at LOA 130.0 months (10y 10mo) for the top 20 per cent and 102.5 months (8y 6mo) in the lower 20 per cent: log‐rank test score 0.035 ( p <0.05). The most socially deprived were diagnosed earlier and started steroids earlier. Of those of South Asian heritage, 18 per cent declined steroids, compared with 9 per cent of white British heritage. Also, 44 per cent of those of South Asian heritage stopped steroids compared with 17 per cent of those of white British heritage. Interpretation: Patients from South Asian and deprived backgrounds had earlier LOA. Genetic disease modifiers are likely to be implicated, but social and cultural factors influence access to treatment. What this paper adds: Males of South Asian heritage with Duchenne muscular dystrophy (DMD) stop walking earlier than those of white British heritage. The most deprived children with DMD lose ambulation earlier than the least deprived. Children from South Asian backgrounds are more likely to decline or stop steroids. This article is commented on by Langer and Kirschner on pages780–781 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.